Reproducibility of indirect persistent inward current indicators with neuromuscular electrical stimulation - Timothée Popesco; Davide D'Amato Brunetta; Stefano Pata; Nicolas Place (Current Issues in Sport Science)
Introduction Neuromuscular electrical stimulation (NMES) has been validated as an efficient tool to train and evaluate the neuromuscular system. Recently, it has been used to estimate persistent inward currents (PICs) in motoneurons (Donnelly et al., 2021). Notably, PICs play an important role in motor unit behavior (Heckman & Enoka, 2012) and are thought to be involved in the centrally mediated responses to NMES. This study aimed to examine the reproducibility of indirect PIC indicators, such as extra force production during wide-pulse high-frequency (WPHF) NMES, sustained electromyographic (EMG) activity following WPHF NMES and force production in response to Achille’s tendon vibration combined with NMES.